Prognostic and Predictive Value of DAMPs and DAMP-Associated Processes in Cancer - Fucikova, Jitka; Moserova, Irena; Urbanova, Linda; Bezu, Lucillia; Kepp, Oliver; Cremer, Isabelle; Salek, Cyril; Strnad, Pavel; Kroemer, Guido; Galluzzi, Lorenzo; Spisek, Radek (Frontiers in Immunology, 2015)
It is now clear that human neoplasms form, progress and respond to therapy in the context of an intimate crosstalk with the host immune system. In particular, accumulating evidence demonstrates that the efficacy of most, if not all, chemo- and radiotherapeutic agents commonly employed in the clinic critically depends on the (re)activation of tumor-targeting immune response. One of the mechanisms whereby conventional chemotherapeutics, targeted anticancer agents and radiotherapy can provoke a therapeutically relevant, adaptive immune response against malignant cells is commonly known as „immunogenic cell death“ (ICD). Importantly, dying cancer cells are perceived as immunogenic only when they emit a set of immunostimulatory signals upon the activation of intracellular stress response pathways. The emission of these signals, which are generally referred to as „damage-associated molecular patterns“ (DAMPs), may therefore predict whether patients will respond to chemotherapy or not, at least in some settings. Here, we review clinical data indicating that DAMPs and DAMP-associated stress responses might have prognostic or predictive value for cancer patients.